STRATEGI PENGEMBANGAN OBJEK WISATA ALAM GUNUNG FATULEU - Calvin Antonio E Cornelis; Apriana H J Fanggidae; Tarsisius Timuneno (Universitas Nusa Cendana, 2019)
The purpose of this study is to describe tourism development strategies in increasing visits to theMount Fatuleu Nature Tourism object. Research types used are Qualitative Descriptive Research,Where researchers intend to describe existing phenomena by analyzing and presenting systematicfacts to facilitate understanding and withdrawal conclusions. By using Qualitative Methods thenthe data obtained will be more complete, more profound, credible, and meaningful, so the researchobjectives can be achieved. The population in this study included all those who knew and hadvisited Mount Fatuleu Tourism Object in Kupang Regency. In this study, the sample wasadjusted to Roscoe's theory (in Sugiyono, 2007), that the sample size that was feasible in the studywas at least 30 to 500. In this study the method used to analyze was descriptive analysis method toanswer the driving and inhibiting factors development of the Gunung Fatuleu Tourism Object inKupang Regency. Whereas to answer the strategy of developing the Gunung Fatuleu TourismObject in Kupang Regency using a SWOT analysis. Keywords : Tourism Development